Development Of ICC-Box to Enrich Intercultural Communication Among Asian ESL/EFL Speakers - Nor Syamimi Iliani Che Hassan; Siti Ainul Ayzan Ayub; Nor Hairunnisa Mohammad Nor; Wan Muhammad Fitri Wan Amir Nizam (Malaysia Journal of Invention and Innovation, 2025)
Globalization transforms the world into a highly connected and interdependent space. The modern era has expanded globalization practices to the academia. For higher education, global prominence is included as one of the aspirations to strengthen Malaysia as an educational hub. One of the key initiatives suggested is by fostering collaborations with international educational institutions to equip students with instrumental knowledge and skills which they can apply in an increasingly competitive global environment. Nonetheless, globalization can lead to cross-cultural communication issues among students if they have not developed cultural intelligence to help them understand other cultures well. To overcome some of these issues, ICC-Box (Intercultural Communication Box) has been developed and incorporated in oral communication activities in a multicultural classroom which consisted of Malaysian, Chinese and Indonesian students at UiTM Kelantan Branch. A survey was conducted to gather the students’ perceptions of ICC-Box. The results from the survey indicated that the students held positive perception towards intercultural communication, suitability to students, utilitarian, and general learning content attributes of ICC-Box. By adopting the Communicative Language Teaching Approach, ICC-Box offers students the opportunities to interact and learn more about cultural similarities and differences with their international counterparts without feeling highly concerned about their English language competence.